1989
DOI: 10.1007/bf00288815
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selection intensity and population size on percent oil in maize, Zea mays L

Abstract: The effect of selection intensity and population size on the response to selection for percent oil in the grain of maize (Zea mays L.) was evaluated in a replicated experiment over ten cycles of selection. An open-pollinated variety, Armel's Reid Yellow Dent, was divided into subpopulations of 6,10 and 50 plants. Selection proportions of 17% and 5% were imposed upon each subpopulation. Selection was based on the percentage of oil in individual kernels as determined by wide-line nuclear magnetic resonance spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Quantitative genetic variation was related to population size, although there were far fewer data than for allozyme variation. Responses to artificial selection were greater in larger populations of Drosophila melanogaster Jones et al 1968;Hammond 1973;Franklin 1980;Weber 1990;Weber & Diggins 1990), mice (Eisen 1975), and maize (Silvela et al 1989). Phenotypic variation will reflect quantitative genetic variation if environmental variation is similar across populations.…”
Section: Prediction 1 Genetic Variation Wittlin Species Will Be Posimentioning
confidence: 99%
“…Quantitative genetic variation was related to population size, although there were far fewer data than for allozyme variation. Responses to artificial selection were greater in larger populations of Drosophila melanogaster Jones et al 1968;Hammond 1973;Franklin 1980;Weber 1990;Weber & Diggins 1990), mice (Eisen 1975), and maize (Silvela et al 1989). Phenotypic variation will reflect quantitative genetic variation if environmental variation is similar across populations.…”
Section: Prediction 1 Genetic Variation Wittlin Species Will Be Posimentioning
confidence: 99%
“…Intuitively, the ability to analyze smaller samples of grain will yield greater increases in quality per selection generation, since fewer low-quality seeds will be planted in each group. Silvela et al (1989) demonstrated that the rate of oil content gain was significantly greater if breeding selection occurred on a single-kernel basis, as opposed to composite samples containing all kernels on an ear. NIRS single-seed quality analysis has been applied to predict oil and protein content in maize, wheat, and soybeans (Orman and Schumann, 1992;Abe et al, 1995); moisture content in maize, lima beans, peanuts, soybeans, and sunflower (Norris and Hart, 1965;Finney and Norris, 1978;Norris, 1983;Lamb and Hurburgh, 1991); oil content in meadowfoam (Patrick and Jolliff, 1997); oleic and linoleic acid in sunflower (Sato et al, 1995;Velasco et al, 1999a); and oil, protein, glucosinolate content, and oleic, linoleic, and erucic acid concentration in rapeseed (Sato et al, 1998;Velasco et al, 1999b;Velasco et al, 1999c).…”
mentioning
confidence: 99%
“…Effective breeding techniques require accurate, inexpensive and reliable soybean composition analysis. Certain areas of breeding and selection research would also benefit from single soybean seed analysis (Silvela et al, 1989). Conventional composition analysis methods such as the Kjeldahl method for protein measurement and the ether extraction method for oil fraction measurements are timeconsuming, expensive and impractical for measurements on large numbers of soybean samples required for molecular genetic mapping and other selection and breeding studies.…”
Section: Introductionmentioning
confidence: 99%